Analysis of Mathematical Problem-Solving Ability for VII Class Students of SMP During the Covid-19 Pandemic - Boni Harianda; Lilis Diana (Magister Mathematic Education Department Faculty of Teacher Training and Education Universitas Riau, 2021)
The Covid-19 pandemic has greatly impacted various worlds without exception in the field of education, especially in Indonesia. This situation causes learning that is usually done face-to-face to turn into online learning making students find it difficult to understand the material given. This study aims to determine the mathematical problem-solving ability of MTS Thariqul Hidayah students, Indragiri Hulu Regency in class VII MTS Thariqul Hidayah students as many as 25 students and to describe the level of problem-solving ability categories in each item statement of questions that have been given in the form of descriptive questions consisting of 5 questions. The research method uses qualitative descriptive analysis to find out the extent to which the category achievement is based on problem-solving indicators during the covid-19 pandemic. Based on the ability analysis carried out by students in working on mathematical problem-solving questions with Linear Equations and Inequality One variable found that the student problem-solving process is very low. The instrument used is a question that has been tested for reliability, validity, discriminating power, and difficulty. Generally, the achievement of indicators of problem-solving ability has not been fully achieved due to ineffective learning and lack of interaction between teachers and students. The results showed that there were still student errors in solving mathematical problems in each problem-solving indicator.